MECHANISMS FOR INCREASING THE COMPETITIVENESS OF SMALL BUSINESS PRODUCTS AND EXPANDING FOREIGN ECONOMIC RELATIONS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article analyzes the mechanisms for increasing the export potential of small businesses and expanding their foreign economic activity in the context of modernization of the national economy and deepening structural changes. During the study, the transformational factors limiting the integration of small businesses into foreign markets - disruptions in the logistics chain, complexities in the international certification system, and the lack of information and consulting - were systematically considered. The article also puts forward scientific and practical proposals and recommendations on the use of digital platforms, cluster cooperation models, and marketing innovations as modern drivers for accelerating foreign economic relations and ensuring the international competitiveness of small business products.